2014
DOI: 10.1111/vox.12210
|View full text |Cite
|
Sign up to set email alerts
|

The strategies to reduce iron deficiency in blood donors randomized trial: design, enrolment and early retention

Abstract: Background and Objectives Repeated blood donation produces iron deficiency. Changes in dietary iron intake do not prevent donation-induced iron deficiency. Prolonging the interdonation interval or using oral iron supplements can mitigate donation-induced iron deficiency. The most effective operational methods for reducing iron deficiency in donors are unknown. Materials and Methods ‘Strategies To Reduce Iron Deficiency’ (STRIDE) was a two-year, randomized, placebo-controlled study in blood donors. 692 donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…For example, repeated phlebotomy in frequent blood donors may severely deplete iron stores and subsequently interfere with normal erythropoiesis. 5,6 Recent investigations of frequent blood donors have focused primarily on preventative care against iron deficiency anemia, [7][8][9][10][11][12] with limited understanding regarding the impact of frequent donations on RBC characteristics and resilience to cold storage.…”
mentioning
confidence: 99%
“…For example, repeated phlebotomy in frequent blood donors may severely deplete iron stores and subsequently interfere with normal erythropoiesis. 5,6 Recent investigations of frequent blood donors have focused primarily on preventative care against iron deficiency anemia, [7][8][9][10][11][12] with limited understanding regarding the impact of frequent donations on RBC characteristics and resilience to cold storage.…”
mentioning
confidence: 99%
“…The study was designed to evaluate an educational intervention and an iron‐supplementation intervention, each with appropriate controls. As previously described, eligible frequent whole blood or double red blood cell (DRC) donors who were not taking iron supplements were recruited at an enrollment donation. Donors agreed to continue to donate whole blood or DRCs at their previous frequency and, if assigned to the blinded pill arms, not to take any self‐administered iron supplements.…”
Section: Methodsmentioning
confidence: 99%
“…Donors in the pill groups were sent a bottle of pills and instructions after each donation. Details of the blinding method and management of side effects have been previously reported . To allow for compliance assessment, donors were asked to return unused pills or empty bottles from the previous mailing in a postage‐paid envelope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, donors with a ferritin level of not more than 12 ng/mL have severe iron deficiency with no iron in the marrow available for synthesis of new RBCs. During our studies of frequent donors, we have routinely observed subjects who passed the Hb screen and donated 1 unit of blood, only later to find that their predonation ferritin level was not more than 12 ng/mL, confirming that Hb is a poor marker for iron deficiency in blood donors. While ferritin level of not more than 12 ng/mL is a highly specific marker for iron deficiency, it is not a particularly sensitive marker for iron deficiency.…”
mentioning
confidence: 88%